Contingent faculty report - Schulman, Steven, author (Colorado State University. Libraries, 2015)
In Fall 2010, the Coalition for the Academic Workforce surveyed non-tenure track faculty members (also called "contingent" faculty or "adjunct" faculty) in colleges and universities across the United States. 28,974 of these faculty members responded, making the CAW data set one of the largest sources of information available about the characteristics and work conditions of contingent faculty.
Keywords: academic labor markets; adjunct faculty; contingent faculty; higher education; non-tenure track faculty; part-time faculty